PACKAGING DAN LABELING SEBAGAI IDENTITAS PRODUK: UPAYA DIFERENSIASI UMKM DI TENGAH PERSAINGAN PASAR LOKAL (STUDI KASUS UMKM KERIPIK PISANG KEPOK) - Nasrullah, Nasrullah; Syahkirin, M; Amanda, Oce Tia (Jurnal Daya Saing, 2025)
The increasingly intense competition among Micro, Small, and Medium Enterprises (MSMEs) in local markets requires strong differentiation strategies to maintain competitiveness. Packaging and labeling serve as crucial factors in building product identity as well as visual and informational instruments that influence consumer perceptions. This study aims to analyze the effect of packaging and labeling on product differentiation, with product identity as a mediating variable, in the case of banana chips MSMEs. The research employed a quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected through Likert-scale questionnaires distributed to respondents who met the research criteria. The findings reveal that packaging and labeling have a positive and significant influence on both product differentiation and product identity. However, product identity does not significantly mediate the relationship between packaging or labeling and product differentiation. These results indicate that consumers primarily assess product uniqueness directly through packaging and labeling attributes. The study provides practical implications that optimizing packaging and labeling design can serve as an effective differentiation strategy for MSMEs, while also contributing academically to the development of marketing theories based on product identity.